Colour removal from industrial wastewater using bladderwort as adsorption media / Salina Alias, Amalina Amirah Abu Bakar, Nor Azliza Akbar and Siti Normasyarah Muhamed - Alias, Salina; Abu Bakar, Amalina Amirah; Akbar, Nor Azliza; Muhamed, Siti Normasyarah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Adsorption process in wastewater treatment using natural products has become popular due to its low cost and environmentally friendly approach. However, less attention has been focused on the ability of aquatic plant species such as Bladderwort as an adsorption media. This paper discusses the effectiveness of using Bladderwort as a natural adsorbent for the removal of colour from wastewater. Under batch technique, the effect on adsorbent size (75-600 μm), wastewater pH (pH 1-12) and agitation speed (50-250 rpm) was determined. The results indicated that the removal efficiency of colour is in tandem with the size of Bladderwort as higher size particles have more efficiency on removal of colour. Besides, the wastewater pH also plays a major role in the colour removal efficiency where the highest removal was observed in acidic condition compared to alkali. However, the agitation speed is least affected in the removal of colour. The optimum size of Bladderwort and pH to effectively remove the colour was at 600 μm and pH 3.